Quantification of spiral artery remodelling using an Adobe Photoshop-based technique - Otun, H A; Innes, B A; Lash, G E; Schiessl, B; Ball, E; Searle, R F; Robson, S C; Bulmer, J N (Reproduction (Cambridge, England), 2019)
Uterine spiral arteries undergo remodelling in normal pregnancy, with replacement of the musculoelastic arterial media by fibrinoid containing extravillous trophoblast cells. Deficient spiral artery remodelling is associated with several adverse pregnancy outcomes. Although there are distinct components of spiral artery remodelling, assessment is subjective and often based on an overall impression of morphology. We aimed to develop a quantitative approach for assessment of uterine spiral artery remodelling. Placental bed biopsies were immunostained using smooth muscle markers, digital images of spiral arteries were captured and Adobe Photoshop was used to analyse positive immunostaining. The method was then used to investigate variation in the same vessel at different levels within a paraffin block, and the effect of parity, pre-eclampsia or miscarriage on vascular smooth muscle cell content. Results were also compared with a more subjective morphology-based assessment system. There was good intra- and interobserver agreement and the method correlated well with the more subjective assessment system. There was an overall reduction in vascular smooth muscle, as detected by caldesmon 1 (h-caldesmon) immunopositivity, with increasing gestational age from 8 weeks to term. A previous pregnancy did not affect the amount of spiral artery smooth muscle. Comparison of pre-eclampsia and late miscarriage samples with controls of the appropriate gestational age demonstrated increased medial smooth muscle in pathological samples. This technique provides a simple, rapid, reproducible and inexpensive approach to quantitative assessment of spiral artery remodelling in normal and pathological human pregnancy, a process which although fundamental for successful pregnancy, is still incompletely understood.